Dapagliflozin (SGLT2-i) induced euglycaemic diabetic ketoacidosis. Issue 9 (19th September 2019) - Leader, Ross; Cowen, Jake; Rajeev, Surya Panicker
Abstract : Sodium glucose co-transporter-2 inhibitors (SGLT2-i) have become a popular therapeutic strategy in the management of hyperglycaemia in type 2 diabetes mellitus. The primary site of action of SGLT2-i is at the proximal renal convoluted tubule. They work by blocking SGLT2 receptors, sodium-dependent glucose co-transport molecules, which in turn prevents glucose reabsorption, facilitating glucosuria, improving glycaemic control as well as a moderate degree of weight loss. We report the case of a 51-year-old woman admitted to the acute medical unit with abdominal pain and vomiting, who was diagnosed with euglycaemic diabetic ketoacidosis secondary to recent initiation of an SGLT2-i medication (dapagliflozin). Clinicians should be aware of this rare side effect of SGLT2-i, to circumvent delays in patient management.